Advance directives in France: do junior general practitioners want to improve their implementation and usage? A nationwide survey - Sidonie Hubert (BMC Medical Ethics, 2019)
Abstract Background The doctor-patient relationship has evolved to respect “the autonomy and patients’ rights”. One of the cornerstones in such autonomy is the opportunity for patients to draw living wills, also known as advance directives (AD). However, information about AD available to patients remains scarce largely due to the lack of involvement of General practitioners for several reasons. The aim of our study was to evaluate current general practitioner residents’ (GPR) behavior concerning their role in informing their patients about AD. Method We built a French nationwide survey from GPR class of 2012 to 2014. Results Two thousand three hundred ten residents completed our survey (21.1% of the total population of GPR during the period). 89.8% declared their willingness to offer patients the opportunity of writing AD. When asked about the usefulness of AD, 73.6% of residents responded that these are a suitable help for patients, but 19.7% considered that AD are essentially geared towards frail patients. Among residents who want to inform patients about AD (n = 2075), 14.7% wanted to involve all patients. Only 20.5% thought that elderly people should be systematically informed about AD. When the question involves other frail people in various disease areas, information seems relevant for 60.1% of GPR considering patient with cancer or malignant hematologic disease and for 56.2% about patients affected by neurodegenerative disease. When considering the routine use of AD, 20.5% of GPR would take them into account only if they are in agreement with the patient’s decision. Conclusions The results of the survey indicate that GPR would rather choose to decide who should be informed about AD, and when to take AD into account for ethical concerns.